Cultural Networks and Social Inclusion of Migrants in Europe: Heritage, ICT, and Participatory Governance. Issue 4 (1st October 2016) - Innocenti, Perla
Column Editor's Notes: The "Digital Heritage: Spotlight on Europe" column examines technological advances internal and external to cultural institutions. The digital shift changed radically how cultural heritage is made, disseminated, distributed, accessed, consumed, and monetized. One of the most important revolutions is that the user's role changed dramatically, shifting from passive observers to active participants and content producers with many new and exciting opportunities for engagement, creative use, and access. The strength of the column is its broad, international focus, and contributors are encouraged to explore issues and recent advances in digital heritage theories, methodologies, standards relevant to the European region, as well as the larger, global audience. ABSTRACT: This study brings together and critically reflects on the social, policy, and technological contexts within which cultural heritage institutions are addressing current challenges of social inclusion in Europe. It explores the role of cultural networks in helping institutions and their host societies to manage the tensions and realise the opportunities arising from migration. The concept of "migrating heritage" is proposed to tackle this complex interdisciplinary research area.